2020
DOI: 10.1111/1365-2745.13490
|View full text |Cite
|
Sign up to set email alerts
|

Biological Flora of the British Isles:Tilia platyphyllos

Abstract: This account presents information on all aspects of the biology of Tilia platyphyllos Scop. subsp. cordifolia (Besser) C.K. Schneid (Large‐leaved Lime) that are relevant to understanding its ecological characteristics and behaviour: all British native material is this subspecies. The main topics are presented within the standard framework of the Biological Flora of the British Isles: distribution, habitat, communities, responses to biotic factors, responses to environment, structure and physiology, phenology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 82 publications
(115 reference statements)
2
17
0
Order By: Relevance
“…Therefore, the paleoecological data from Lago Verdarolo strongly suggest that the currently widespread (quasi)-monospecific Fagus sylvatica stands of the Northern Apennine montane belt are the outcome of millennia of land-use intensification. Beech took advantage of its lower palatability and sensitivity to fire and browsing compared to other co-existing trees to increase its dominance (Figures 3 , 4 ; Pigott 1991 ; Tinner and others 2000 ; Thomas 2016 ; Leuschner and Ellenberg 2017 ; Thomas and others 2018 ; Rey and others 2019 ). Previous paleoecological and archeological studies in the region suggested that ancient farming favored beech directly because of the use of beechnuts to feed pigs and indirectly by overexploiting competing trees like Ulmus , Tilia , Fraxinus and Abies for foddering (Cruise and others 2009 ; Branch 2013 ; Branch and others 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the paleoecological data from Lago Verdarolo strongly suggest that the currently widespread (quasi)-monospecific Fagus sylvatica stands of the Northern Apennine montane belt are the outcome of millennia of land-use intensification. Beech took advantage of its lower palatability and sensitivity to fire and browsing compared to other co-existing trees to increase its dominance (Figures 3 , 4 ; Pigott 1991 ; Tinner and others 2000 ; Thomas 2016 ; Leuschner and Ellenberg 2017 ; Thomas and others 2018 ; Rey and others 2019 ). Previous paleoecological and archeological studies in the region suggested that ancient farming favored beech directly because of the use of beechnuts to feed pigs and indirectly by overexploiting competing trees like Ulmus , Tilia , Fraxinus and Abies for foddering (Cruise and others 2009 ; Branch 2013 ; Branch and others 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…These conditions are like those forecasted for the near future under the ongoing climatic change (Kovats and others 2014 ), so reviving these ancient Early and Mid-Holocene forests could be a feasible possibility to adapt forests to future conditions (Henne and others 2015 ). This holds particularly true when considering that Fagus sylvatica , the currently dominant tree in the montane belt of the Apennines, is way more sensitive to summer drought than most of the tree species dominating during the warmest period of the Holocene (for example, Abies alba, Fraxinus excelsior, Acer, Tilia, Ulmus ; Pigott 1991 ; Packham and others 2012 ; Thomas 2016 ; Leuschner and Ellenberg 2017 ; Thomas and others 2018 ) and may probably experience increasingly frequent and severe diebacks related to drought (Piovesan and others 2008 ; Dorado-Liñán and others 2019 ). However, future forest management must also consider that in many locations most of the natural components of the Early and Mid-Holocene mixed forests are currently rare or absent after millennia of intense land-use.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of mycorrhizae by T. borchii and T. maculatum is hardly surprising as the fungi have been reported to form ectomycorrhizal symbioses with Tilia spp. elsewhere in Europe [22,60,61].…”
Section: Plos Onementioning
confidence: 99%
“…Tilia are insect pollinated species, flowering relatively late in the season after the leaves have fully expanded. In Central Europe this is late June for T. platyphyllos and for T. cordata about 10 days later, early July (Pigott, 2012(Pigott, , 2020. They take at least 20 years to flower and reproduce sexually, but in dense woodland this may be much later (Pigott, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…T. platyphyllos has a more limited distribution, ranging from Italy and Greece in the south to Denmark in the north, and Romania in the east to the United Kingdom in the west (Logan et al, 2019;www.euforgen.org). Tilia is host for many species, such as birds, insects and lichen (Pigott, 2020). Tree stems become hollow after about 200 -300 years and form suitable nesting sites for e.g.…”
Section: Introductionmentioning
confidence: 99%